Nuclear DNA Content Variation among Central European Koeleria Taxa - PECINKA, ALES (Oxford University Press, 2006)
• Background and Aims Polyploidization plays an important role in the evolution of many plant genera, including Koeleria. The knowledge of ploidy, chromosome number and genome size may enable correct taxonomic treatment when other features are insufficient as in Koeleria. Therefore, these characteristics and their variability were determined for populations of six central European Koeleria taxa. • Methods Chromosome number analysis was performed by squashing root meristems, and ploidy and 2C nuclear DNA content were estimated by flow cytometry. • Key Results Three diploids (K. glauca, K. macrantha var. macrantha and var. pseudoglauca), one tetraploid (K. macrantha var. majoriflora), one decaploid (K. pyramidata) and one dodecaploid (K. tristis) were found. The 2C nuclear DNA content of the diploids ranged from 4·85 to 5·20 pg. The 2C DNA contents of tetraploid, decaploid and dodecaploid taxa were 9·31 pg, 22·89 pg and 29·23 pg, respectively. The DNA content of polyploids within the K. macrantha aggregate (i.e. within K. macrantha and K. pyramidata) was smaller than the expected multiple of the diploid genome (K. macrantha var. macrantha). Geography-correlated variation of DNA content was found for some taxa. Czech populations of K. macrantha var. majoriflora had a 5·06 % smaller genome than the Slovak ones. An isolated eastern Slovakian population of K. tristis revealed 8·04 % less DNA than populations from central Slovakia. In central and north-west Bohemia, diploid and tetraploid cytotypes of K. macrantha were sympatric; east from this region diploid populations, and towards the west tetraploid populations were dominant. • Conclusions Remarkable intra-specific inter-population differences in nuclear DNA content were found between Bohemian and Pannonian populations of Koeleria macrantha var. majoriflora and between geographically isolated central and eastern Slovakian populations of K. tristis. These differences occur over a relatively small geographical scale.